2006
DOI: 10.1002/prot.20995
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of (−)‐epigallocatechin‐3‐gallate with human serum albumin: Fluorescence, fourier transform infrared, circular dichroism, and docking studies

Abstract: (-)-Epigallocatechin-3-gallate (EGCG), the major constituent of green tea has been reported to prevent many diseases by virtue of its antioxidant properties. The binding of EGCG with human serum albumin (HSA) has been investigated for the first time by using fluorescence, circular dichroism (CD), Fourier transform infrared (FTIR) spectroscopy, and protein-ligand docking. We observed a quenching of fluorescence of HSA in the presence of EGCG. The binding parameters were determined by a Scatchard plot and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
97
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 33 publications
14
97
1
1
Order By: Relevance
“…EGCG was shown to exert antiamyloid activity by influencing cellular signal transduction pathways and reactive oxygen species (27). However, EGCG also directly binds to hydrophobic protein sequences both by hydrophobic interactions and by hydrogen bonding (28) and has been demonstrated to directly inhibit fibril formation of a wide range of amyloidogenic proteins (2-6). In the past, various small molecules have been shown to inhibit or reverse amyloid formation in vitro (9,26).…”
Section: Resultsmentioning
confidence: 99%
“…EGCG was shown to exert antiamyloid activity by influencing cellular signal transduction pathways and reactive oxygen species (27). However, EGCG also directly binds to hydrophobic protein sequences both by hydrophobic interactions and by hydrogen bonding (28) and has been demonstrated to directly inhibit fibril formation of a wide range of amyloidogenic proteins (2-6). In the past, various small molecules have been shown to inhibit or reverse amyloid formation in vitro (9,26).…”
Section: Resultsmentioning
confidence: 99%
“…A previous report has shown that the hydrophobicity of the catechins obtained for a 1-octanol/PBS binary liquid was increased drastically by the presence of the galloyl moiety (19). On the other hand, studies of serum albumin-polyphenol interactions suggest that binding of polyphenols with serum albumin are stabilized by hydrophobic interactions, hydrogen-bonding forces, and electrostatic forces (20,21). HSA is a globular protein composed of three structurally similar domains (I, II, and III), each containing a number of hydrophobic cavities.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, by first allowing for the formation of amyloid fibrils or inhibition thereof in a controlled environment in vitro, we avoid interference by active molecular chaperones, such as clusterin and BSA, which are readily present as nutrients in cell medium. 44,64,65 After incubation of the treated cells for 48 h, the treatment mixture was removed and 100 μL of serum-free medium containing MTT (0.6 mM) was added to each well. The cells were then incubated for an additional 2 h, and the MTT-containing medium was replaced with 100 μL of DMSO.…”
Section: Solution-state 1 H Nmr Spectroscopymentioning
confidence: 99%